Characterizing Traffic Performance in Cellular Networks - Rivas Tocado, Francisco Javier; Díaz-Zayas, Almudena; Merino-Gómez, Pedro (IEEE, 2014)
The characterization of traffic performance in cellular networks from the user viewpoint is a costly process involving a large range of protocols and parameters with complex dependencies. Dealing with this challenge requires cross-layer measurements and correlated analysis. The characterization methodology proposed here supports the collection of key information for troubleshooting IP communications problems and correlating them with propagation issues, such as cell changes or link outages, and resource allocation problems at specific geographical locations. The methodology is based on a monitoring and recording tool for smartphones and a correlation tool chain. With the results obtained from the methodology's deployment, mobile operators, services providers, and mobile developers could gain access to real user experiences and specific users' data to improve radio coverage, adapt services, and customize mobile applications and protocols based on IP to cope with mobility issues in cellular networks. keywords: {Mobile computing;Mobile communication;IP networks;Smart phones;Internet;High performance computing;Performance evaluation;mobile Internet;performance;monitoring;characterization;tools;methodology;mobile applications;cross layer;cellular networks;mobility;high-speed railways}, URL: https://ieeexplore.ieee.org/stamp/stamp.jsp?tp=&arnumber=6655871&isnumber=6756719
Keywords: Sistemas de comunicaciones móviles; Mobile computing; Mobile communication; IP networks; Smart phones; Internet; High performance computing; Performance evaluation; Mobile Internet; Performance; Monitoring; Characterization